TANGGUNG JAWAB PELAKU USAHA ATAS INFORMASI SUATU PRODUK MELALUI IKLAN YANG MENGELABUI KONSUMEN - Shinta Kurnia Dewi, Ni Putu; Gatrawan, I Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
This paper entitled “Entrepeneur’s Liability on Information a Product ThroughThe Poisoning This Consumer Advertising”. This paper uses normative methods andthe statute approach. In an effort to attract consumers to increase sales of its products,entrepreneur their products through advertising. However, it is often found thatadvertising provides information about a product which can not be verified so thatentrepreneur be betraying the trust of consumers. Consumers who feel aggrievedentitled to sue for damages and demand liability from entrepeneur.
Keywords: Liability, Entrepeneur, Advertising, Consumer